Lorain Police Department: A Study to Improve Patrol Deployment - Brewer, Steven L (2014)
The Lorain (OH) Police Department requested research assistance from the Ohio Consortium of Crime Science (OCCS) for the purpose of evaluating and revising the current patrol districts and the allocation of resources within the districts. The OCCS is an association of researchers from universities and state agencies working together to provide evidence-based solutions to the real-world problems faced by local criminal justice agencies. The goal of the project was to evaluate and revise the current police districts and the allocation of resources within those districts. The first objective in support of the project goal was to assess calls for service, officers’ workload, hotspots, and violent crimes within the existing police districts. The second objective in support of the project goal was to develop new police districts based on the findings of the first objective and to predict future calls for service, officers’ workload, hotspots, and violent crimes within those proposed districts. Calls for service data (N = 56,423) from the Lorain Police Department’s computer-aideddispatch (CAD) system were analyzed for the year 2013. Findings indicate that there is disparity in allocation of patrol resources and calls for service workload across the five current police districts within the city of Lorain. The CHAID algorithm was employed to group 93 existing geographic section tracts within the city into twelve statistically similar groups. Geospatial patterns readily emerged and the five police districts were reconfigured into four new patrol beats. Four recommendations are presented: (1) the proposed new police beats should be implemented; (2) section tracts within the new beats should be used as crime analysis targets; (3) patrol resources should be specifically assigned to each of the new beats on all shifts; and, (4) patrol operations should be fully integrated within the new CAD system scheduled for implementation in early 2015